2016
DOI: 10.3846/13923730.2016.1177586
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Evaluation of Railway Aggregate Sub-Ballast Gradation and Other Properties Variation

Abstract: The use of high quality aggregate mixture, proper technological parameters of laying and compacting as well as the required thickness of the mixture ensures railway sub-ballast layer properties. In this paper gradation, den­sity and water permeability of 49 produced random samples of aggregate sub-ballast (ASB) mixture which were taken from the stockpile in the plant and from the uncompacted railway layer are investigated. The statistical parameters of the ASB mixture quality indicators and histograms with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Therefore, the arithmetic mean, calculated for each sieve by each of those three methods, differs. Usually, gradation of aggregate or aggregate mixture is expressed in percent passing through the sieves (Navikas et al, 2016). Statistical indicators of percent passing of the granite aggregates through separate laboratory sieves, histograms and theoretical curves of normal distribution are presented in Figure 2 below.…”
Section: Investigation Of Granite Aggregates Gradation Variationmentioning
confidence: 99%
“…Therefore, the arithmetic mean, calculated for each sieve by each of those three methods, differs. Usually, gradation of aggregate or aggregate mixture is expressed in percent passing through the sieves (Navikas et al, 2016). Statistical indicators of percent passing of the granite aggregates through separate laboratory sieves, histograms and theoretical curves of normal distribution are presented in Figure 2 below.…”
Section: Investigation Of Granite Aggregates Gradation Variationmentioning
confidence: 99%
“…It has been found that a weak railway subgrade may cause instability of the railway track system [7]. The problem of modelling railway track substructure has also been considered [8,9]. Krakovskiy et al [10] and Xu et al [11] described the evaluation of the technical condition of the rails, while Povilaitienė et al [12] described the possibility of decreasing rail wearing on the railway curve.…”
Section: Multiple Criteria Evaluation and The Inverse Hierarchy Modelmentioning
confidence: 99%
“…The main reasons for ballast degradation are ballast fragmentation and wear. They destine settlement of a road and increase expenses for maintenance of track geometry (Navikas et al 2016;Tennakoon et al 2014). The indicator of particles resistance to fragmentation, the coefficient of Los Angeles Abrasion (LAA), is determined by applying Los Angeles Abrasion test under standard (LST EN 1097-2:2010).…”
Section: Resistance To Fragmentation and Wearmentioning
confidence: 99%